Peningkatan Hasil Belajar dan Keaktifan Mahasiswa Melalui Strategi Pembelajaran Peta Konsep Pada Mata Kuliah Evolusi - Dharma Ferry (Journal on Education, 2022)
This research aims to describing the implementation of concept map teaching and learning in evolution course in State Islamic Institut of Kerinci. This research focused on improving student achievement on cognitive domain through the implementation of the concept mapping strategy. Research subjects are biology students, amounting to 24 students. This type of research is classroom action research. The research instrument is a learning device (syllabus, lesson plan, and textbook), data was collecting by test and observation paper. Based on the result of the study, found that student achievement in the cognitive domain and student activity in general has increased after the implementation of concept map strategy in evolution course. The results showed that the average score of the students average in the first cycle 66,75 (enough) and student activity 66 % (enough) increased to 72,70 (excellent) for student achievement and 76% for student activity on the second cycle. The result also showed that student achievement on cognitive aspect have increased after the implementation of concept map teaching and learning strategy in evolution course.